Transformasi Digital E-Commerce Dalam Menguasai Kosentrasi Pasar di Indonesia - Abdan Sifa; Isti Masruroh; Muhamad Abdan Zulfa; Sirfi Nur Fitriani; Naerul Edwin Kiky Aprianto (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This article discusses the current development of e-commerce in Indonesia. The evolution of e-commerce in Indonesia has had a significant impact on the concentration of the technology industry, creating a dynamic and competitive ecosystem. With ever-increasing internet penetration and widespread adoption of digital technologies, e-commerce platforms are not only revolutionizing the way consumers shop, but also driving innovation and growth in other sectors. This development provides opportunities for business actors, both large and small, to reach a wider market and introduce their products in a more efficient way. This article also discusses the impact of the development of e-commerce in Indonesia. This article highlights the factors that influence the rapid development of e-commerce, where collaboration between government, industry players and society will be the key to maximizing the potential of e-commerce and supporting inclusive digital economic growth in Indonesia. By utilizing existing technology, Indonesia has the potential to become a major player on the global e-commerce map, leading innovation and creating sustainable added value.